PENGARUH BUDAYA ORGANISASI DAN KERJASAMA TIM TERHADAP KINERJA TATA USAHA - Yosef Rizal (Manajer Pendididikan, 2015)
The purpose of this study was to analyze the influence of organizational culture and teamwork on administrative performance Junior High School. The research result shows that all variables have positive influence on the performance in the form of a linear equation = 21.645 + 0,396.X_1 + 0,430.X_2, where all independent variables have significant influence with sig 0.000 < 0.05. Furthermore, the R-square value of 0.644 indicates 64.4% of the variance Administrative Performance in Junior High School Seluma influenced by factors Organizational Culture andTeamwork, and 35.6% are influenced by other factors that have not researched yet.Keywords: organizational culture, cooperation and teamwork, administration, performance.